1997
DOI: 10.1001/archneur.1997.00550180070015
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Antioxidants and Parkinson Disease

Abstract: Our data suggest that a high intake of dietary vitamin E may protect against the occurrence of PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
136
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(138 citation statements)
references
References 36 publications
1
136
0
1
Order By: Relevance
“…There was no significant association between PD and flavonoid intake reported by one cross-sectional study (de Rijk et al 1997a).…”
Section: Fruits Vegetables and Antioxidantsmentioning
confidence: 74%
See 2 more Smart Citations
“…There was no significant association between PD and flavonoid intake reported by one cross-sectional study (de Rijk et al 1997a).…”
Section: Fruits Vegetables and Antioxidantsmentioning
confidence: 74%
“…One cross-sectional study is included because the methods were similar to the CC studies, and because it was included in one of the published meta-analyses (de Rijk et al 1997a). The quality of evidence is not as strong, but results are presented as supporting evidence.…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…In three US case-control studies [487,489,501], no associations of PD with vitamin C, E, A (or carotenoid) intake were reported. Similarly, retrospective data from the Rotterdam study showed no associations of PD with vitamin C or beta-carotene intake, although an inverse association with vitamin E intake was reported (OR 0.3, 95% CI 0.1-0.9 for the highest versus the lowest tertile, p for trend 0.03) [502]. A population-based case-control study conducted in Washington found no associations for vitamin C, E, A, or beta-carotene intake in the initial study [488] nor in an extended dataset [492].…”
Section: Antioxidantsmentioning
confidence: 94%
“…Watanabe et al [211] reported that G. biloba supplementation in mice had neuromodulatory effects as indicated by a more than three-fold increase of mRNA expression for neuronal tyrosine/threonine phosphatases-1, microtubule-associated tau, prolactin, different calcium, and chloride channels as well as transthyretin. Flavonoidassociated antioxidant interventions have also been proposed to be beneficial in hypoxia/ischemia, seizures, Parkinson's disease, increased survival in brain cancers, and general age-related neurodegeneration [50,73,89,125]. However, since the flavonoids used in these studies were given as food extracts or preparations containing other potential bioactive or antioxidant components rather than as a pure flavonoid fraction, the results may not reflect solely the effects of flavonoids.…”
Section: Flavonoids: Neuroprotective Agents In Vivo and In Vitro?mentioning
confidence: 99%